The relationship between admission Braden score and poor prognosis in Sepsis patients: evidence from the MIMIC-III database - Ding, Tingting; Zhao, Lei; Hu, Ben; Wei, Xing; Wang, Yongsheng; Wang, Yan (BMC infectious diseases, 2025)
The measurement of Braden score can be used as a useful tool for clinical care. However, the relationship between the Braden score and clinical outcomes in sepsis patients remains unclear. This study aims to investigate the association between the Braden score and clinical outcomes in sepsis patients. The Medical Information Mart for Intensive Care III (MIMIC-III) database was searched to identify patients with sepsis who had their Braden score measured. The primary outcomes were 28-day, 60-day, and 90-day mortality. Multivariate Cox regression analysis was used to clarify the relationship between Braden score and primary outcomes, and Kaplan-Meier survival analysis and stratified analysis were used to verify our findings. A total of 8,290 patients were included in our study, during the 28-day, 60-day, and 90-day follow-up periods, mortality was recorded in 1,554, 1,938, and 2,173 patients, those with lower Braden score had a 58% increased risk of 28-day mortality (hazard ratio [HR] 1.58; 95% confidence interval [CI] 1.38, 1.81), a 50% increased risk of 60-day mortality(HR 1.50; 95% CI 1.33,1.70), and a 52% increased risk of 90-day mortality(HR 1.52; 95% CI 1.35,1.70). Patients with lower Braden score received more mechanical ventilation and vasopressors, and presented with elevated WBC counts and lactate levels. In addition, lower Braden scores were also linked to increased adjusted ICU mortality and a higher incidence of AKI within the first seven days following ICU admission. Lower Braden score is an independent risk factor for mortality in critically ill patients with sepsis. Braden score can be used as a potential indicator for assessing outcomes in such patients.